Performance comparison of stirred media mill and ball (BOND) mill in bauxite grinding. (18th May 2020) - Hacıfazlıoğlu, Hasan; Korkmaz, Abdul Vahap
Abstract: Nowadays, the demand for a finer grind in mineral processing has set new challenges within the industry, particularly for grinding technology. Apart from a finer grind, energy efficiency is also a key driver in optimizing grinding technology. With increasing need for fine and ultrafine grinding, stirred media mills became an alternative for conventional ball mills. In this study, samples of bauxite whose chemical composition and Hardgrove Index values are known were ground to micronized size by a laboratory scale stirred media mill and its performance was compared with a laboratory scale ball (Bond) mill. Stirred media mill decreased bauxite d50 size from 780 to 5 µm in 3 min. But, the ball mill has reduced to 455 µm at the end of the same grinding period. In addition, the energy consumed by the ball mill for similar fineness (5 µm) was approximately 300 kWh/t energy, whereas the stirred media mill consumes approximately 174 kWh/t energy. As a result, the stirred mill consumed less energy because it could grind in a shorter time.